Huge Cavernous Hemangiomas Enveloping the Optic Nerve Successfully Removed by a Vertical Lid Split Orbitotomy - Jung-Hoon Yum; Yoon-Duck Kim; Jung Hye Lee; Kyung In Woo (Case Reports in Ophthalmological Medicine)
A 63-year-old woman presented with a 15-year history of gradually increasing proptosis of right eye. Ocular examination revealed proptosis of 9 mm with decreased visual acuity in her right eye. CT scan showed a well-circumscribed and enhancing orbital mass filling almost the entire right orbit. The tumor occupied the superolateral, superomedial, and inferomedial intraconal space, enveloping the optic nerve. Complete excision of two large intraconal tumors was performed successfully via a vertical lid split orbitotomy. Histopathologic examination confirmed the diagnosis of cavernous hemangioma. There were no intraoperative or postoperative complications. The patient achieved a satisfactory cosmetic outcome 1 year after surgery.